Household expenditure patterns in the rural areas of Oyo State, Nigeria: evidence of rural households vulnerability to food insecurity - Ogundapo, A.T.; Manyong, Victor M.; Kormawa, P.M.; Fabiyi, Y. (2008)
The changes in household income result in a rapid shift in composition of food demanded by the food-secure and food-insecure households. In this paper, we applied popular AIDS model to estimate the budget shares and determinant factors of demand for different food groups. The analysis of food security status reveals that 21 per cent only of the rural households were food secured while the large majorities (79%) were food in-secured. Household income and the prices of various food groups affected the demand for a specific group of food. The budget share indicates an increase in households’ food expenditure as the level of income decreases. Conversely, the per capita expenditure on food is directly correlated with income level. Roots and tubers remain the major staples in Oyo State, Nigeria, but interestingly, poor households rely more on cereals and fruit and vegetables than rich households. The high level of vulnerability suggests that broad-based agricultural interventions and pro-poor poverty reduction schemes remain the key to poverty reduction.